Choosing environmentally friendly dish soap in medan: price and environmental considerations - Mutahajjid, Zul Azmi; Effendi, Ihsan; Sugito, Sugito (Institute of Computer Science (IOCS), 2024)
This research aims to analyze the influence of price and environmental concern on the intention to purchase environmentally friendly dishwashing soap products in Medan Denai District. This research uses quantitative methods with simple random sampling techniques. Data was collected through questionnaires distributed to 98 respondents in Medan Denai District. Data were analyzed using multiple linear regression. The research results showed that there was a positive and significant influence between price and environmental concern on the intention to purchase environmentally friendly dish soap products. This means that the lower the product price, the higher the consumer's purchase intention to buy that product. In addition, the higher the level of consumer environmental awareness, the higher their purchasing intention to buy environmentally friendly products. This research has implications for producers and marketers of environmentally friendly dish soap products. Manufacturers need to pay attention to competitive pricing and marketing strategies that focus on increasing consumers' environmental awareness. Marketers need to emphasize the benefits and advantages of environmentally friendly products in an effort to increase consumer purchasing intentions